1996
DOI: 10.1007/bf00439116
|View full text |Cite
|
Sign up to set email alerts
|

Study of the role of iron in the anticryptococcal activity of human serum and fluconazole

Abstract: Anticryptococcal activity of human serum and apotransferrin in RPMI 1640 was studied in vitro. The effects of varying concentrations of FeCl3 on this activity was investigated. Possible synergy of serum and apotransferrin with fluconazole was also measured. The fungistatic activity of human serum, whether lyophilized, stored at 4 degrees C, fresh frozen or purchased from commercial sources vs. Cryptococcus neoformans was comparable. There was no significant loss of fungistatic activity after freezing and thawi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2010
2010

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…There were some indications in the literature that the C. neoformans-inhibitory activity of serum was due to the iron binding capacity of serum (9,10,17). Reversal by FeCl 3 is demonstrable with freshly prepared (3, 5) but not stored (9) reagent, presumably due to absorption, reduction, or complexing of ferric ion in stored material.…”
mentioning
confidence: 99%
“…There were some indications in the literature that the C. neoformans-inhibitory activity of serum was due to the iron binding capacity of serum (9,10,17). Reversal by FeCl 3 is demonstrable with freshly prepared (3, 5) but not stored (9) reagent, presumably due to absorption, reduction, or complexing of ferric ion in stored material.…”
mentioning
confidence: 99%
“…In these studies we found human serum (10%) in RPMI‐1640 inhibited growth of C. albicans and this inhibition is completely reversed by iron overload (10 μ m FeCl 3 ). Grover et al reported previously [6] that inhibition of C. neoformans growth by 10% human serum was not reversed by 10 μ m FeCl 3 , though partial reversal was noted in some present experiments performed concurrently with CSF experiments. There was also at least partial reversal, by iron overload, of inhibition of C. neoformans and C. albicans growth by 50% CSF in preliminary studies, a point currently under more extensive study.…”
Section: Discussionmentioning
confidence: 99%